2014
DOI: 10.1007/s00109-014-1156-z
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous points of control over regulatory T cells

Abstract: Posttranslational modification by ubiquitin tagging is crucial for regulating the stability, activity and cellular localization of many target proteins and processes including DNA repair, cell cycle progression, protein quality control and signal transduction. It has long been appreciated that ubiquitin-mediated events are important for certain signaling pathways leading to leukocyte activation and the stimulation of effector function. It is now clear that the activities of molecules and pathways central to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 149 publications
(177 reference statements)
0
3
0
Order By: Relevance
“…A deeper understanding of the molecular determinants of Tregs in avian species will facilitate the therapeutic manipulation of these cells. As a major transcriptional factor in the transcriptomic landscape of mammalian Tregs, FoxP3 is an obvious target for small molecule, antibody and chimeric therapies of the future [ 59 63 ]. Demonstration of the impact of FoxP3 in avian Tregs would pave the way for a raft of new therapies for diseases that not only impose a significant welfare burden, but also costs the global poultry industry millions of dollars in lost revenue [ 64 – 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…A deeper understanding of the molecular determinants of Tregs in avian species will facilitate the therapeutic manipulation of these cells. As a major transcriptional factor in the transcriptomic landscape of mammalian Tregs, FoxP3 is an obvious target for small molecule, antibody and chimeric therapies of the future [ 59 63 ]. Demonstration of the impact of FoxP3 in avian Tregs would pave the way for a raft of new therapies for diseases that not only impose a significant welfare burden, but also costs the global poultry industry millions of dollars in lost revenue [ 64 – 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tregs are characterized by their expression of CD4, CD25 and FoxP3, the latter of which is a key transcription factor for the development of Tregs and their immunnosuppressive capabilities. 66 Two main subsets of Tregs have been identified, including natural Tregs, which are produced in the thymus, and adaptive Tregs, which are induced from naïve T cells in the periphery in response to chronic exposure to antigen. Induced Tregs are prominent in the tumor microenvironment, where they expand in response to VEGF, CXCL12, IL-10, and TGF-β and are capable of producing a number of immunosuppressive signals, including adenosine and prostaglandin E 2 .…”
Section: Cellular and Extracellular Components Of Tumor Nichesmentioning
confidence: 99%
“…Recently, it has been demonstrated that Foxp3 maintenance is also affected by inflammatory cytokines and other factors, which alter post-translational modifications such as ubiquitination, acetylation, and phosphorylation thus regulating the stability of the cellular pools of Foxp3 (14). Indeed, Foxp3 stability has been linked to the activities of the deubiquitinase USP7 and ubiquitinase STUB1, which respectively avoid or promote Foxp3 proteasome degradation (15, 16). Thus, in addition to the transcriptional control of foxp3 expression, other mechanisms of regulation contribute to the overall abundance and activity of Foxp3, affecting the functions of Tregs and therefore the maintenance of self-tolerance.…”
Section: Introductionmentioning
confidence: 99%